Eight weeks of core stability training improves landing kinetics for freestyle skiing aerials athletes - Wei, M.; Fan, Y.; Lu, Z.; Niu, X.; Wu, H. (Frontiers in Physiology, 2022)
Freestyle skiing aerials are characterized by technical elements including strength, flexibility and balance. Core stability in aerials can improve sporting performance. Objective: This study aimed to analyze the effect of 8weeks of core stability training on core stability performance in aerials. Methods: Participants were randomly assigned to a control group (CG; n = 4male + 5female; age 15.89 ± 1.54years; height 163.11 ± 6.19cm; weight 55.33 ± 5.07Kg) and a training group (TG; n = 4male+5female; age 16.11 ± 2.47years; height 161.56 ± 5.25cm; weight 57.56 ± 8.11Kg). Body shape, the performance of core stability, and landing kinetics were measured after 8weeks of core stability training. Independent sample t-tests were used to compare baseline values between groups. A two-way repeated-measures analysis of variance (ANOVA) (time × group) was used. Results: The TG improved body shape, and waist circumference (t = -2.333, p = 0.020). Performance of core stability, squat (t = -4.082, p = 0.004), trunk flexion isometric test (t = -4.150, p = 0.003), trunk lateral bending isometric test (t = -2.668, p = 0.008), trunk rotation isometric test (t = -2.666, p = 0.008), side bridge (t = -2.666, p = 0.008), back hyperextension (t = -4.116, p = 0.003), single foot triple jump (t = -4.184, p = 0.003), and single-leg balance with eyes closed (t = 4.167, p = 0.003). Performance in landing kinetics, End/Phase (t = -4.015, p = 0.004), sagittal axes (t = -4.598, p = 0.002), frontal axis (t = 3.116, p = 0.014), peak power hip changing range (t = 2.666, p = 0.017), peak power knee changing range (t = 2.256, p = 0.049). Conclusion: Core stability training leads to improvements in body shape, the performance of core stability, and landing kinetics. Therefore, these improvements can improve the sporting performance in aerials competitions.